2015
DOI: 10.1039/c5ra20097k
|View full text |Cite
|
Sign up to set email alerts
|

Order-enhanced silver nanowire networks fabricated by two-step dip-coating as polymer solar cell electrodes

Abstract: The efficient utilization of Ag NW by avoiding their aggregation and multi-layer stacking in their networks can improve the optical and electrical properties of the derived transparent conductive electrodes (TCEs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…As a result, potentially more conductive and simultaneously more transparent meshes are obtained in the case of higher aspect ratios of the nanowires. 35 Aside from random NW mesh electrodes, there is quite a range of reports on the preparation of electrodes based on aligned NWs, which either self-assemble in dip coating processes 36,37 or by using etching techniques. 38 The resulting electrodes with aligned metal NWs have been shown to afford a lowered sheet resistance and a reduced roughness compared to random NW networks.…”
Section: General Considerationsmentioning
confidence: 99%
“…As a result, potentially more conductive and simultaneously more transparent meshes are obtained in the case of higher aspect ratios of the nanowires. 35 Aside from random NW mesh electrodes, there is quite a range of reports on the preparation of electrodes based on aligned NWs, which either self-assemble in dip coating processes 36,37 or by using etching techniques. 38 The resulting electrodes with aligned metal NWs have been shown to afford a lowered sheet resistance and a reduced roughness compared to random NW networks.…”
Section: General Considerationsmentioning
confidence: 99%
“…Thus, due to the restricted translational and rotational degree of freedom in z-direction, the withdrawn AgNWs may be aligned as we know it from chromosome combing in biophysics 21 . Recently such alignment of AgNWs caused by dip-coating was observed 11 22 . Furthermore the superiority of dip-coating over spray-coating with regard to resulting optoelectrical performance was shown.…”
mentioning
confidence: 99%
“…It has been reported that AgNWs can be orderly deposited on solid substrate by using the grazing incidence spraying method (scheme shown as Figure S3 in Supporting Information) . Using these ordered AgNWs (Figure S4 a) as templates, it is possible to prepare aligned APS line patterns, which could also be used for assembly of small molecules and nanoparticles, generating corresponding aligned line patterns (optical image of the assembled AuNPs was shown as Figure S4 b).…”
Section: Figurementioning
confidence: 99%
“…[37] These AuNPs patterns provide at unable plasmonic structure, which has potential applications in the fields of SERS sensing and nanophotonics.It has been reportedt hat AgNWsc an be orderly deposited on solid substrate by using the grazing incidence spraying method (scheme shown as Figure S3 in Supporting Information). [39][40][41] Using these ordered AgNWs (Figure S4 a) as templates, it is possible to prepare alignedA PS line patterns, which could also be used for assembly of small molecules and nanoparticles, generating corresponding aligned line patterns (opticali mage of the assembled AuNPs was shown as Figure S4 b). In addition, more complex molecular patterns could also be preparedb yc ontrolling the assembly of AgNWs.The assembled nanoparticle patterns could be used for SERS detection.…”
mentioning
confidence: 99%